Randomized evaluation of live attenuated vs. inactivated influenza vaccines in schools (RELATIVES) cluster randomized trial: Pilot results from a household surveillance study to assess direct and indirect protection from influenza vaccination. Issue 38 (11th September 2015) - Kwong, Jeffrey C.; Pereira, Jennifer A.; Quach, Susan; Pellizzari, Rosana; Dusome, Edwina; Russell, Margaret L.; Hamid, Jemila S.; Feinberg, Yael; Winter, Anne-Luise; Gubbay, Jonathan B.; Sirtonski, Brittany; Moher, Deanna; et al.
Abstract Background Children are key drivers of influenza transmission. Vaccinating school age children decreases influenza in the community. Objective To pilot-test the methods for a future trial to compare the direct and indirect benefits of inactivated influenza vaccine (IIV) vs. live attenuated influenza vaccine (LAIV) in preventing influenza infection. Methods During the 2013–14 influenza vaccination campaign, we piloted an open-label cluster randomized trial involving 10 elementary schools in Peterborough, Ontario, Canada. We randomized schools on a 1:1 basis to have students receive IIV or LAIV. We invited a subset of vaccinated students and their households to participate in a surveillance sub-study, which involved completing daily symptom diaries during influenza season and collecting mid-turbinate swabs from symptomatic individuals to detect influenza infection. The main outcome measure was confirmed influenza infection using a real-time reverse transcriptase polymerase chain reaction (PCR) assay. Results One hundred and nineteen households (166 students and 293 household members) participated. During 15 weeks of surveillance, we detected 22 episodes of PCR-confirmed influenza (21 influenza A/H1N1 and 1 influenza B). The incidence of influenza per 1000 person-days was 1.24 (95% CI, 0.40–2.89) for IIV-vaccinated students, compared to 0.13 (95% CI, 0.003–0.72) for LAIV-vaccinated students; the incidence rate ratio was 0.10 (95% CI, 0.002–0.94). Similarly, the incidence of influenza per 1000 person-days was 1.33 (95% CI, 0.64–2.44) for IIV household members, compared to 0.47 (95% CI, 0.17–1.03) for LAIV household members; the incidence rate ratio was 0.36 (95% CI, 0.11–1.08). The overall incidence rate ratio (combining students and household members) was 0.27 (95% CI, 0.09–0.69). Conclusions Household surveillance involving participant monitoring and reporting of symptoms and self-collection of mid-turbinate swabs is feasible. A larger study is required to validate the suggestion that vaccinating children with LAIV might confer more protection against influenza for both children and their household contacts, compared to IIV. Trial registration: ClinicalTrials.gov NCT01995851.